2017
DOI: 10.1007/s40124-017-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

New Insights and Perspectives in Congenital Diarrheal Disorders

Abstract: Purpose of Review We highlight new entities of congenital\ud diarrheal disorders (CDDs) and progresses in understanding\ud of functionally related genes, opening new diagnostic and\ud therapeutic perspectives.\ud Recent Findings The more significant advances have been\ud made in field of pathogenesis, encouraging a better under-\ud standing not only of these rare diseases but also of more com-\ud mon pathogenetic mechanisms.\ud Summary CDDs represent an evolving group of rare chronic\ud enteropathies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However according to the data, HSCT did not cure SD/THE, except possibly for the immune defects, but is associated with high mortality (2/4). Thus SD/THE is clearly different from defects in intestinal immune-related homeostasis like immunodysregulation polyendocrinopathy enteropathy, X-linked (IPEX) or IPEX-like disorders where either immunosuppressant drugs or HSCT could be useful (36).…”
Section: Discussionmentioning
confidence: 99%
“…However according to the data, HSCT did not cure SD/THE, except possibly for the immune defects, but is associated with high mortality (2/4). Thus SD/THE is clearly different from defects in intestinal immune-related homeostasis like immunodysregulation polyendocrinopathy enteropathy, X-linked (IPEX) or IPEX-like disorders where either immunosuppressant drugs or HSCT could be useful (36).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital diarrheal disorders (CDDs) include defects in digestion and absorption, enterocyte structure, neuroendocrine differentiation and intestinal immune homeostasis [8]. Deficiencies in digestion and absorption of carbohydrates, proteins or fat account for the majority of CDDs [3,8]. DGAT1-related diarrhea, an autosomal recessive disorder first described in 2012, impairs triglyceride absorption [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in digestion and absorption of carbohydrates, proteins or fat account for the majority of CDDs [3,8]. DGAT1-related diarrhea, an autosomal recessive disorder first described in 2012, impairs triglyceride absorption [6,8]. DGATs (acyl CoA:diacylglycerol acyltransferases) convert diacylglycerides to triglycerides by adding an acyl-CoA moiety, a crucial and final step in triacylglycerol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…CDDs are rare, mostly autosomal recessive inherited enteropathies that typically early onset with varying severity and prognostic features [5]. In the etiology of CDDs which are associated with high risk of mortality and morbidity; Over 30 CDD disordes and 35 responsible genes have been identified that cause defects in nutrients and electrolytes digestion, absorption, enterocyte structures, intestinal immunerelated homeostasis and enteroendocrine cell development [6].…”
mentioning
confidence: 99%